Developing speed / Nationa Strength and Conditioning Association ; Ian Jeffreys, editors. - Jeffreys, Ian (Sport performance series., 2025)
Athletes in all sports rely to greater or lesser degree on speed, whether it involves sprinting down the track or chasing a loose ball, speed often contributes to overall athletic ability. 'Developing Speed' is an elite-level guide to speed development, regardless of the sport involved.